Digital Consumer Debt and Mental Well-Being in Generation Z: A Scoping Review - Grace Fresania Kaparang; Cherry Lumingkewas; Shapely Ambalao (Economics and Digital Business Review, 2026)
The rapid expansion of digital financial services, particularly Buy Now Pay Later (BNPL), online lending platforms, and e-commerce credit systems, has transformed consumption patterns among Generation Z. Although these services improve financial accessibility and transactional convenience, concerns have emerged regarding their psychological consequences, including anxiety, financial stress, compulsive buying behavior, and declining mental well-being. This scoping review aims to map existing evidence regarding the relationship between digital consumer debt and mental well-being among Generation Z consumers. This review employed the PRISMA Extension for Scoping Reviews (PRISMA-ScR) framework. Relevant articles published between 2019 and 2025 were identified from Google Scholar, Scopus-indexed journals, PubMed, and ScienceDirect using keywords related to BNPL, digital debt, fintech lending, Generation Z, and mental health. Inclusion criteria focused on empirical and review-based studies discussing digital borrowing behavior and psychological outcomes among young adults and Generation Z populations. A total of 15 eligible studies were analyzed. The findings indicate that digital consumer debt is consistently associated with elevated financial stress, anxiety symptoms, impulsive purchasing tendencies, emotional instability, and reduced financial well-being among Generation Z users. Several studies also highlight the role of financial literacy, self-control, and social media influence as moderating factors affecting borrowing behavior. Furthermore, easy accessibility and low perceived borrowing barriers contribute to debt normalization among younger consumers. The rapid expansion of fintech lending ecosystems therefore requires balanced approaches that simultaneously promote financial innovation, consumer accessibility, and psychological well-being protection. Without adequate financial literacy and responsible regulatory frameworks, the continued normalization of digital consumer debt may increase mental health vulnerabilities among younger generations in increasingly digitalized societies. This review concludes that while digital lending technologies provide short-term economic flexibility, excessive reliance on consumer debt may negatively influence mental well-being among Generation Z. Policymakers, educational institutions, and fintech providers should strengthen financial literacy initiatives and implement responsible lending regulations to minimize psychological risks associated with digital debt exposure.